High-order magnetohydrodynamics for astrophysics with an adaptive mesh refinement discontinuous Galerkin scheme - Guillet, Thomas; Pakmor, Rüdiger; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. Modern astrophysical simulations aim to accurately model an ever-growing array of physical processes, including the interaction of fluids with magnet
Gesehen am 27.05.2019